V.1 - "Pandey, Viraj Kumar" (New Delhi, 2007)
India is the home of religion, philosophy, and spirituality. In every age, she provides the world with her armies of spiritual masters, and teachers. This work covers chapters that deal with problems in metaphysics and epistemology, some are in the fields of ethics.
Keywords: Philosophy-India